Increasing the efficiency of the use of forest resources by the digitalization of forest education. Issue 1 (October 2020) - Mushkarova, O; Mikheeva, M; Tereshchenko, S; Panyutin, A; Kuznetsov, E
Abstract: Currently, the problem of increasing the efficiency of the use of forest resources is urgent. One of the factors affecting the efficiency of the use of forest resources is the quality of the human capital of the forest sector.It is necessary to develop the key competencies of employees and future employees of the forestry sector using various forms of training. In recent years, forestry education has been actively developing based on the use of the digital technologies. The article presents the results of surveys of students on their perception of a new form of education, students' assessment of the possibility of high-quality mastering of material in distance learning and the difficulties they face. Conclusions are also made on how digitalization of forestry education will improve the efficiency of the human capital of forest sector organizations which will affect the efficiency of the use of forest resources in Russia.